The skeleton of the Triassic anomodont Kannemeyeria wilsoni Broom - Cruickshank, Arthur R I (Bernard Price Institute for Palaeontological Research, 1975)
The general structure of the post-cranial skeleton of many Triassic anomodonts is now well known, but in Africa that of the stratigraphically important Lower Triassic (? Scythian) genus Kannemeyeria is known only from dissociated elements. A brief description is given for the first time of an almost complete skeleton ascribed to this genus. The environment of deposition is described briefly. The locality of the type species of the genus is also noted .
Keywords: Dicynodontia; Beaufort Group; Postcranial skeleton